Providence of fire - Staveley, Brian (Staveley, Brian. Chronicle of the Unhewn Throne, 2015)
The world of the Annurian Empire is an ambitiously drawn one. Adare, Valyn, and Kaden, the three children of the assassinated emperor, go their separate ways and find themselves embroiled in inevitable conflict.